Development of Learning Media Hören A2WEB-Based - Risnovita Sari; Rina Evianty (BIRCU, 2022)
This research is entitled Development of Learning MediaranHoeren A2Website based. The background of this research is the low skills of students in the Hoeren A2 course (listening skills level A2) due to the lack of learning media. The purpose of this research is to produce a website-elearning learning media product using the ADDIE development model (Analysis, Design, Development, Implimentation, Evaluation). At the Design stage, an outline of the website content is made, the preparation of the website framework. In Development, website creation, website packaging and presentation, quiz design, testing by media experts and material experts are carried out. At the implementation stage, tests were carried out on small and large classes and at the evaluation stage, it included indicators of media success that evaluated each stage of development. Making media using Articulate Storyline 3 software which consists of material text, images, videos, audio, animations, practice questions and quizzes.